Seasonal Alterations in Organic Phosphorus Metabolism Drive the Phosphorus Economy of Annual Growth in F. sylvatica Trees on P-Impoverished Soil - Netzer, Florian; Herschbach, Cornelia; Oikawa, Akira; Okazaki, Yozo; Dubbert, David; Saito, Kazuki; Rennenberg, Heinz (Frontiers in Plant Science, 2018)
Phosphorus (P) is one of the most important macronutrients limiting plant growth and development, particularly in forest ecosystems such as temperate beech (Fagus sylvatica) forests in Central Europe. Efficient tree internal P-cycling during annual growth is an important strategy of beech trees to adapt to low soil-P. Organic P (Porg) is thought to play a decisive role in P-cycling, but the significance of individual compounds and processes has not been elucidated. To identify processes and metabolites involved in P-cycling of beech trees, polar-metabolome and lipidome profiling was performed during annual growth with twig tissues from a sufficient (Conventwald, Con) and a low soil-P (Tuttlingen, Tut) forest. Autumnal phospholipid degradation in leaves and P-export from senescent leaves, accumulation of phospholipids and glucosamine-6-phosphate (GlcN6P) in the bark, storage of N-acetyl-D-glucosamine-6-phosphate (GlcNAc6P) in the wood, and establishing of a phospholipid ‘start-up capital’ in buds constitute main processes involved in P-cycling that were enhanced in beech trees on low-P soil of the Tut forest. In spring, mobilization of P from storage pools in the bark contributed to an effective P-cycling. Due to the higher phospholipid ‘start-up capital’ in buds of Tut beeches, the P-metabolite profile in developing leaves in spring was similar in beech trees of both forests. During summer, leaves of Tut beeches meet their phosphate (Pi) needs by replacing phospholipids by galacto- and sulfolipids. Thus, several processes contribute to adequate Pi-supply on P-impoverished soil thereby mediating similar growth of beech at low and sufficient soil-Pi availability.